Effects of anabolic implants, marbling, and tenderness on consumer acceptability and purchasing decisions for beef - Platter, William J., author; Tatum, J. Daryl, advisor; Belk, Keith E., committee member; Engle, Terry E., committee member; Koontz, Stephen R., committee member; Smith, Gary C., committee member (Colorado State University. Libraries, 2003)
This research was designed to study the effects of repetitive use of anabolic implants on beef carcass quality, tenderness, and consumer ratings for palatability. Data from consumer sensory panels and experimental auctions conducted in this study also were used to examine the effects of marbling score and Wamer-Bratzler shear force (WBSF) on consumer acceptability and purchasing decisions for beef. Crossbred steers (n = 550) were randomly assigned to a non-implanted treatment or to one of ten lifetime implant treatments where cattle were implanted at some or all of five phases of production (branding, weaning, backgrounding, feedlot entry, or re-implant time). Non-implanted steers produced carcasses with higher (P < 0.05) marbling scores and steaks with lower (P < 0.05) WBSF values and more desirable (P < 0.05) consumer tenderness ratings. Implanting steers at branding, weaning, or backgrounding did not affect marbling scores, consumer ratings for like/dislike of steak tenderness, or percentage of consumers rating overall eating quality of steaks as satisfactory. Steaks from non-implanted steers were rated as more desirable (P < 0.05) for overall eating quality than steaks from steers implanted two, three, four, or five times. The predicted probability for consumer acceptance of steaks increased approximately 10% for each full marbling score increase between Slight to Slightly Abundant. The predicted probability for consumer acceptance of steaks dramatically decreased as steak WBSF value increased from 3.0 to 5.5 kg. Changes in WBSF within the high (> 5.5 kg) or low (< 3.0 kg) portions of the range of WBSF values had little effect on the predicted probability of consumer acceptance of steaks. On average, premium Choice steaks received a $0.40/kg premium and Prime steaks received a $1.12/kg premium over the mean bid price for Select steaks. Predicted mean bid prices for steaks decreased $ 1.02/kg for each 1 kg increase in WBSF value. Collectively, results of these studies suggest that anabolic implant protocols can affect beef palatability traits, such as marbling and tenderness, and differences in marbling and shear force impact the level of overall consumer acceptance and value of beef.
Keywords: livestock; animal sciences